An MR-compatible device for automated and safe application of laser stimuli in experiments employing nociceptive stimulation - Pott, Peter Paul; Kamping, Sandra; Bomba, Isabelle; Diesch, Eugen; Flor, Herta; Schwarz, Markus (Journal of neuroscience methods, 2010)
In this paper the establishment of an automatic laser application device that reproducibly delivers laser stimuli in a safe, controlled, and reliable manner is presented. Nociceptive stimulation is widely used in functional magnetic resonance imaging (fMRI) experiments and a number of different methods are employed. One major advantage of laser stimulation as a method to administer painful stimuli is that it selectively activates nociceptors. To avoid damage to the subject's skin, which might occur if the same skin area were stimulated too often, the laser focal spot needs to be repositioned after each stimulus. Here, we describe the design of the mechanical set-up, the functionality, the computation of laser stimulus intensity, the materials used, the monitoring system, and the interface to the control software. Additionally, MR-compatibility and functionality of the device were evaluated and assessed in a 3T MR scanner. Finally, the reliability and validity of the device were tested and demonstrated. It permits easy and investigator-independent use of laser stimulation in the MR scanner.